Reproductive health and access to services among rural-to-urban migrants in China - Zhenzhen Zheng; Ciyong Lu; Liming Lu (United Nations Research Institute for Social Development (UNRISD), 2013)
Reproductive health, including maternal health, is an important issue for Chinas migrant population. This paper briefly reviews the reproductive health situation, including reproductive health knowledge and status, health service use, and interventions among rural-to-urban migrants. By analysing three data sets, the authors assess the reproductive health status of migrants, focusing particularly on the self-reported reproductive health of migrant women; maternal health and service utilization of migrant women; and contraceptive use among migrant men. Their three surveys found the following common themes in terms of migrant reproductive health services: migrants were found to have limited access to health service or poor health-seeking behaviour in some aspects of reproductive health; they often have relatively limited sources of service compared to local residence; and their knowledge and information about reproductive health service is not adequate. There have been some improvements over time, in some cases through project intervention. Further research is needed to assess the impact of policy change and other variety of efforts to improve migrants reproductive health.
Keywords: 330